Computer Classification of Linear Codes Based on Lattice Point Enumeration - Kurz, Sascha; Kurz, Sascha (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2024)
Linear codes related to applications in Galois Geometry often require a certain divisibility of the occurring weights. In this paper we present an algorithmic framework for the classification of linear codes over finite fields with restricted sets of weights. The underlying algorithms are based on lattice point enumeration and integer linear programming. We present new enumeration and non-existence results for projective two-weight codes, divisible codes, and additive F4-codes.
CRIS-Team Scopus Importer:2024-08-16
Keywords: classification; enumeration; integer linear programming; lattice point enumeration; linear codes; two-weight codes